Influence of preoperative depression on clinical outcomes after cervical laminoplasty: A retrospective study - Zhang, Wentao; Sun, Tianze; Wang, Shiyuan; Zhang, Jing; Yang, Ming; Li, Zhonghai (Frontiers in Surgery, 2023)
Background: Depression is a highly prevalent mental disorder, and we found that patients with preoperative depression had worse postoperative improvement in lumbar fusion. Are mental factors related to the prognosis of laminoplasty? Objective: To analyze the relationship between depression and clinical outcomes after laminoplasty for the treatment of multilevel CSM. Methods: In this retrospective study, 115 patients with multilevel cervical spondylotic myelopathy (CSM), who underwent laminoplasty and were followed up for more than 1 year, were enrolled in this study from October 2018 to October 2021. Patients with the scores of 21-item Beck Depression Inventory (BDI) ≥15 or Hamilton Depression Scale-24 (HAMD-24) >20 were included in the depression group. The clinical outcomes were evaluated by the changes and recovery rate (RR) of Japanese Orthopaedic Association Scores (JOA) and Neck Disability Index (NDI) respectively. Univariate and multiple linear regression analyses were performed to reveal the relationship between preoperative depressive states and clinical outcomes. Results: Fourteen patients were diagnosed with depression by BDI and twenty-nine by HAMD-24. Between the depression group and the non-depression group, the age, gender, smoking history, and duration of symptoms were statistically significant (P<0.05). Multiple linear regression showed that the BDI scores had a negative relationship with the changes and RR of JOA and NDI, and the HAMD-24 scores had a negative relationship with the changes and RR of JOA. Conclusions: Preoperative depression in patients with multilevel CSM can lead to worse prognosis. In order to improve the curative effect of the operation, we should pay attention to the psychological state monitoring and intervention of patients before they receive laminoplasty.